Desafíos para la formación profesional del abogado para la ciudadanía global - Hurtado Magán, Giovana Iris (2023)
Four experts in educational policies were interviewed to collect data on the challenges that professional training has to develop global citizenship. The methodological approach used is hermeneutic, through content analysis regarding the two established a priori categories: professional training and global citizenship. From all this, it is concluded that educational policies should guide professional training for global citizenship, designing academic programs in which the student's ability to resolve adverse and complex situations is fostered. Therefore, a change is required in the way of designing, implementing and executing educational policies so that they transcend governments and interests, and that educational leadership is appreciated at all levels, through the reassessment of the teacher as an agent of that change.